Cinegrafias de professoras: formação, autonomia e imaginário social - Severo, Bianka de Abreu (2021)
This Master's dissertation in Education was developed in Line of Research 1 – Teaching, Knowledge and Professional Development, of the Post-Graduation Program in Education (PPGE), at the Federal University of Santa Maria (UFSM). It arose from the interest in bringing the imaginary closer to the autonomous and heteronomous movements permeated in the images that teachers have or produce around teaching. The general objective was to understand the construction of autonomy and the formative paths in the experience of teachers with cinema. The theoretical foundation included studies in the theoretical field of the Social Imaginary (CASTORIADIS, 1982, 2004, 2006, 2009; OLIVEIRA, 2005), Teacher Training (FERRY, 2004; GATTI et al, 2019; NÓVOA, 2009) and Cinema and Education (BERGALA, 2008; FRESQUET, 2013; TEIXEIRA et al 2014). The research-training methodology (JOSSO, 2004) was carried out in seven collective meetings with cinema, in virtual format, between june and july 2020, with the co-authorship of four teachers of Basic Education. The co-author's cinematographies, that is, the narratives based on the appreciation or creation of films, were understood by the hermeneutic analysis (GADAMER, 1997) and, thus, constructed the research results. In general, cinematographies have shown that teachers are attentive to heteronomous movements, however, teaching is largely limited to individual autonomy. The cinematographies of the letter-films, in particular, highlighted desires, strangeness, resistance and a creative reading of the teaching images. Regarding the symbolic place of teachers, society assigns a “task” place, while teachers assign an intellectual place. Thus, teaching is made of a living matter that, in the micro-revolutions, tensions movements of agreement and subversion in the context that circumscribes it, operating a life between the desired and the possible, in which watching and making films are favorable experiences for the expansion of subversive movements. The research indicated that thinking about the formative paths through the sensitive path of images is potent both for the exercise of autonomy and for self-training.